DETERMINACIÓN DE PARENTESCO EN ALPACAS (Vicugna pacos) POR MEDIO DEL ANÁLISIS DE ADN MICROSATÉLITE - Rodríguez B., Jorge (2004)
Ten polymorphic microsatellites for alpacas and llamas were used to evaluate paternity in 47 alpacas (18 crias, 18 mothers and 11 fathers) registered at IVITA-Maranganí Research Station, Canchis Province (Cusco-Peru). Analysis was carried out using two methodologies: Automatic Sequencer (ABI 377 DNA sequencers®) and silver staining techniques. Microsatellites were amplified in three multiple and ten single PCR reactions. The number of alleles varied between 4 and 20. The allelic frequencies and the exclusion probability were calculated using Cervus 2.0. All loci, except for two, were within the range published elsewhere. The accumulated exclusion probability for the ten loci was 0.9999. For each multiplex reaction the accumulated exclusion probability was more than 0.90. Both methodologies yielded the same results. The results confirmed paternity in 18 cases of parent-cria pairs, however in 22% of cases (n=4) were identified alternative parents than those indicated in farm records.